If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = -10x Solving 24 = -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 24 + 10x = -10x + 10x Combine like terms: -10x + 10x = 0 24 + 10x = 0 Add '-24' to each side of the equation. 24 + -24 + 10x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 10x = 0 + -24 10x = 0 + -24 Combine like terms: 0 + -24 = -24 10x = -24 Divide each side by '10'. x = -2.4 Simplifying x = -2.4
| 7-2=3x-18 | | X*(x+7)=411 | | f(0)=(2x-5)2 | | 8n+1=4n-14 | | X*x+7=411 | | 4(3z-1)-4(z+8)=5(z+1) | | 3-2(x+2)=3 | | 20*6-18*6-6=12 | | 1/2x^2-36=0 | | 5(2x-11)=3x+9 | | 3/5.22 | | 4(x+1)-2(-x-1)=0 | | 12+10=10+12 | | 6x-30+1=0 | | 3-7(-x+5)=2x+5 | | 40(x)+60(y)=1700 | | 8(x-1)-2(3x+4)=0 | | 4x^2+9y^2-8x-54y-59=0 | | ln(3x+2)-ln(2)=1 | | ln(x^3+x^2-2)=ln(x-1)(x^2-1) | | X+2x-1=11 | | 10x-24=4x | | x^2=8-9x | | 3.25n+2=3n+6 | | -3x+6=-6x | | 5y+11=(3y+7) | | 4w(7w+3)=0 | | -2x+9x+5=0 | | 4x^4+36x^3= | | (t+2)(6t+1)=0 | | 7.5x-2.5=20.0 | | 11x+37=90 |